Nondestructive measurement of pectin polysaccharides using hyperspectral imaging in mulberry fruit. (1st January 2021) - Yang, Liang; Gao, Huaqi; Meng, Liuwei; Fu, Xiaping; Du, Xiaoqiang; Wu, Di; Huang, Lingxia
Highlights: HSI was used to rapidly and noninvasively measure pectin polysaccharides in mulberry. Four kinds of pectin of mulberries were predicted and DASP and TSP had better results. Different storage temperatures of mulberries for HSI model calibration were evaluated. Two spectral ranges of HSI for pectin prediction were obtained and compared. Predictive capabilities of HSI models for two mulberry cultivars were different. Abstract: Pectin polysaccharide is an important phytochemical with potential biomedical applications. It is commonly measured by time-consuming destructive chemical methods. This work demonstrates the feasibility of using visible and near-infrared hyperspectral imaging (HSI) techniques to rapidly measure pectin polysaccharides in intact mulberry fruits. Based on spatial information provided by HSI images, the representative spectrum of each whole mulberry was accurately extracted without background. The effects of storage temperature on two varieties of mulberries for model establishment were studied. The performances of two spectral ranges obtained by Si and InGaAs CCD detectors for pectin prediction were compared. The best predictions were obtained from dilute alkali soluble pectin and total soluble pectin in Dashi mulberry fruit stored at room temperature, with residual predictive deviation values of 2.317 and 1.935, respectively. Our results show that HSI is a promising alternative to the chemical method to rapidly and nondestructively measure the pectin content.